2019
DOI: 10.3390/electronics8030297
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Magnetic Flux Density on the Cross-Section of a Transformer Core

Abstract: In this paper, the magnetic flux density distribution on the cross-sections of a transformer core is studied. The core for this study consists of two identical U-shaped cores joint at their open surfaces with known air gaps. The magnetic flux density at one of their joint boundary surfaces was measured for different air gaps. A finite element model (FEM) was built to simulate the magnetic flux density and compared with experiment data. Using the validated FEM, the distributed magnetic flux density on the cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…When the magnet is held stationary inside the loop, there is no current in the loop. Based on his observations, Faraday concluded that the induced current is related to the changing magnetic field [7].…”
Section: Faraday's Lawmentioning
confidence: 99%
See 1 more Smart Citation
“…When the magnet is held stationary inside the loop, there is no current in the loop. Based on his observations, Faraday concluded that the induced current is related to the changing magnetic field [7].…”
Section: Faraday's Lawmentioning
confidence: 99%
“…The focus of Lenz's law is the direction of the current induced in a circuit by the effect of a magnetic field. According to Lenz's law, the current generated in the coil counteracts the flux change caused by the moving magnet [7]. The mechanical linkage produces linear movement in the solenoid by reversing the Lenz Law.…”
Section: Lenz's Lawmentioning
confidence: 99%
“…Additionally, the distribution function of the leakage flux will change in correspondence with any winding structural changes as well as the vibration response function of the winding. As a result, the distributed vibration on the winding strongly depends on the mechanical properties of the winding [18].…”
Section: Vibration Transmission Pathsmentioning
confidence: 99%
“…3 The attractive force of the magnetic attachments is proportional to the square of magnetic flux density and it is optimized by the magnetic circuit. 17,18 However, the magnetic flux of the dental magnets were 0.01-0.03 T with the keeper, and the amount of magnetic flux beyond the abutment tooth was only 0.005 T which is much lower than the magnetic field of TMS. 19 Though the open circuit has extended magnetic flux lines with decreased magnetic flux density, while the close circuit has closer magnetic flux lines with increased magnetic flux density, 20 the magnetic field from dental magnets is lower than that of TMS.…”
Section: Introductionmentioning
confidence: 96%